Polyarthritis following vaccination in four dogs - Kohn, B.; Garner, M.; Lübke, S.; Schmidt, M. F. G.; Bennett, D.; Brunnberg, L. (Veterinary and Comparative Orthopaedics and Traumatology, 2003)
The purpose of this study was to describe four dogs that developed polyarthritis (PA) shortly after vaccination.Between 1996–1999, 27 dogs were admitted to the Clinic for Small Animals, University of Berlin with clinical signs of PA. Based on the history, clinical findings, results of routine laboratory tests, radiography and ultrasonography, synovial fluid analysis, serum titers for rheumatoid factors, infectious disease and immunological serum titers nine dogs were diagnosed with idiopathic PA type I and 14 dogs with other forms of polyarthritis. Vaccine-associated PA (VAPA) was suspected in four dogs of different breeds (1.3–2.4 years old) which showed a sudden onset of lameness with several painful and swollen joints three – 15 days (mean 11) after vaccination. Synovial fluid analysis revealed nucleated cell counts ranging from 4,000-72,000/μl (mean 30,000) with 30–90% (mean 80) neutrophils. Treatment consisted of NSAIDs and doxycycline. The VAPA dogs quickly recovered in one to two days, three had not experienced a recurrent arthritic episode, one dog developed arthritic signs 12 days after revaccination. An accurate vaccination history is important on all dogs presenting with PA. In accordance with anecdotal reports the signs of disease in VAPA can spontaneously resolve.
Keywords: Polyarthritis; vaccine-associated; outcome